PENGARUH BRAND AWARENESS, BRAND IMAGE DAN MEDIA COMMUNICATION TERHADAP MINAT NASABAH MEMILIH BANK BRI SYARIAH KCP CILEUNGSI - Fitri Yana Salam; Rafika Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
This research was conducted to determine the effect of brand awareness, brand image and communication media on customer interest in selecting the Bank BRISyariah KCP Cileungsi. This research is quantitative which is the data has been used in this research is form of numbers. This research was conducted by distributing questionnaires to 65 respondents where the respondent is a customer funding of Bank BRISyariah KCP Cileungsi obtained from sampling techniques using purposive sampling techniques and the data collected is processed using the SPSS analysis tool version 24.The result show that there is a simultaneous influence between brand awareness, brand image dan media communication on the customer’s interest in selecting Bank BRISyariah KCP Cileungsi. F-test or partial test results show that brand awareness, brand image and media communication have a significant positive effect on customer interest in selecting Bank BRISyariah KCP Cileungsi. While the brand image do not effect the customer’s interest in selecting Bank BRISyariah KCP Cileungsi.